Accommodation, Accumulation, and Migration of Defects in Ti3SiC2 and Ti3AlC2 MAX Phases. Issue 10 (19th August 2013) - Middleburgh, Simon C.; Lumpkin, Greg R.; Riley, Daniel; Zhon, Y.
<x xml:space="preserve">Abstract</x> We have determined the energetics of defect formation and migration in Mn+1AXn phases with M = Ti, A = Si or Al, X = C, and n = 3 using density functional theory calculations. In the Ti3SiC2 structure, the resulting Frenkel defect formation energies are 6.5 eV for Ti, 2.6 eV for Si, and 2.9 eV for C. All three interstitial species reside within the Si layer of the structure, the C interstitial in particular is coordinated to three Si atoms in a triangular configuration (C–Si = 1.889 Å) and to two apical Ti atoms (C–Ti = 2.057 Å). This carbon–metal bonding is typical of the bonding in the SiC and TiC binary carbides. Antisite defects were also considered, giving formation energies of 4.1 eV for Ti–Si, 17.3 eV for Ti–C, and 6.1 eV for Si–C. Broadly similar behavior was found for Frenkel and antisite defect energies in the Ti3AlC2 structure, with interstitial atoms preferentially lying in the analogous Al layer. Although the population of residual defects in both structures is expected to be dominated by C interstitials, the defect migration and Frenkel recombination mechanism in Ti3AlC2 is different and the energy is lower compared with the Ti3SiC2 structure. This effect, together with the observation of a stable C interstitial defect coordinated by three silicon species and two titanium species in Ti3SiC2, will have important implications for radiation damage response in these materials.